2020
DOI: 10.3390/cells9010257
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy Is a Novel Tumorigenesis-Related Activity of Multifunctional Translationally Controlled Tumor Protein

Abstract: Translationally controlled tumor protein (TCTP) is highly conserved in eukaryotic organisms and plays multiple roles regulating cellular growth and homeostasis. Because of its anti-apoptotic activity and its role in the regulation of cancer metastasis, TCTP has become a promising target for cancer therapy. Moreover, growing evidence points to its clinical role in cancer prognosis. How TCTP regulates cellular growth in cancer has been widely studied, but how it regulates cellular homeostasis has received relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 92 publications
(130 reference statements)
0
14
0
Order By: Relevance
“…Over the past decade, autophagy has been recognised as a central biological process, essential for maintaining cellular homeostasis; but the involvement of TCTP in this pathway has only recently been investigated. In the 'TCTP book', this aspect of TCTP function has only briefly been touched on in two articles [5,34] and also here, we will not cover it in much detail, since another review article in this Special Issue discussed the role of TCTP and autophagy in relation to tumorigenesis [51].…”
Section: Biological Stress Reactions and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, autophagy has been recognised as a central biological process, essential for maintaining cellular homeostasis; but the involvement of TCTP in this pathway has only recently been investigated. In the 'TCTP book', this aspect of TCTP function has only briefly been touched on in two articles [5,34] and also here, we will not cover it in much detail, since another review article in this Special Issue discussed the role of TCTP and autophagy in relation to tumorigenesis [51].…”
Section: Biological Stress Reactions and Autophagymentioning
confidence: 99%
“…The mechanisms of regulated degradation of the TCTP protein were reviewed in detail in [34] and were also covered in a review article in this Special Issue in Cells [51]. Here, we will just briefly summarise the few cases known today (Table 2).…”
Section: Regulation Of Protein Degradationmentioning
confidence: 99%
“…Autophagy is a mechanism that damages, degenerates or aging protein and organelles in cells are transported to the lysosome for digestion and degradation, leading to the basal turnover of cell components and providing energy and macromolecular precursors [6]. A growing body of research suggests that autophagy genes have a large potential to serve as promising markers in the diagnosis, prognosis, and personalized targeted therapies [7][8][9]. Autophagy mechanisms described in endometrial cancers, including the role of PI3K/AKT/mTOR, AMPK-mTOR, and p53 signaling pathways that trigger or inhibit this process, which may become a potential molecular target in clinical treatment methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that autophagy supports the survival and proliferation of cancer cells and metastasis-related behavior (12). Knocking out the FIP200 gene, which is essential for autophagy, inhibited the initiation, progression, and metastasis of breast cancer (12). Inhibition of autophagy using HCQ and Lys05 decreased the proliferation and metastasis of melanoma cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, autophagy enables tumor metabolism and growth, promotes the survival of tumor cells under hypoxic conditions as well as tumorigenesis and induces resistance against therapeutic agents (2,4,10,11). Previous studies have indicated that autophagy supports the survival and proliferation of cancer cells and metastasis-related behavior (12). Knocking out the FIP200 gene, which is essential for autophagy, inhibited the initiation, progression, and metastasis of breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%